Assessing English writing needs for civil engineering students: evidence from a Philippine college - Sittie Aina T. Pandapatan; Abdullah H. Edris; Johara D. Alangca-Azis; Stephen A. Fadare; Al-nor D. Ansao; Basmah S. Hussain (Institute of Advanced Engineering and Science, 2026)
This study examined the perceived English writing needs of civil engineering students at a private higher education institution in the Philippines. Using a quantitative, descriptive, cross-sectional survey design, data were collected from 216 second- to fourth-year students through purposive sampling and a validated 15-item writing needs questionnaire. The instrument demonstrated strong internal consistency, and the data were analyzed using descriptive statistics. The findings showed that students reported substantial needs in both foundational writing skills and field-related written outputs. The most strongly perceived needs were related to grammar, sentence clarity, idea development, and the writing of engineering reports, executive summaries, formal letters, and memoranda. These results suggest that general English instruction alone may be insufficient to address the disciplinary communication demands of civil engineering. The study highlights the need to integrate discipline-specific writing support into the curriculum to strengthen students’ academic writing, professional communication, and workplace readiness.